Customer Relationship Management and Machine Learning Technology for Identifying the Customer - Hidra Amnur (Society of Visual Informatics, 2017)
Customer Relationship Management needed for the company to know their customer more closed, and make two-way communication between company and customer. in CRM solutions are multi-criteria decision-making analysis tools that do not require prior assumptions to explore the weights and performances among project risk, project management and organization performance, based on research framework of stimulus-organism response model. in this study, Machine learning with Support Vector Machine algorithm is currently for classification task due to its ability to model nonlinearities CRM Solutions. With Machine Learning and CRM, Bank X optimize their profit, with manage their more benefit customer or find a new customer or get their lost potential customer back.